Ecological condition and management status of Community Forests in Indian western Himalaya. (October 2021) - Pathak, Ravi; Thakur, Shinny; Negi, Vikram S.; Rawal, Ranbeer S.; Bahukhandi, Amit; Durgapal, Kamini; Barola, Anjali; Tewari, Deep; Bhatt, Indra D.
Abstract: Community Forests (CFs) are considered as an important means of forest management, biodiversity conservation, poverty reduction and ecological sustainability all across the world. Present study is an attempt to understand if CFs in west Himalayan part of India (referred as Van Panchayat) is effective in performing such role of conservation and sustainable flow of goods and services. A total of 31 representative Van Panchayat Forests (VPFs) in western Himalaya were investigated to assess: (i) the ecological condition, and (ii) their status of management. In addition review of available literature was also carried out to understand global trends of knowledge on CFs, and to specifically know the focus of studies on VPs in the study region. A total of 1158 documents on CFs were obtained, of which 91 pertained to VPs/VPFs. These 91 studies were considered for detail assessment. Analysis of published literature on VPFs indicated larger leaning towards management and governance. However, in recent years (2011 onward) a shift towards ecological processes and climate change mitigation was noticed. Overall, the studied VPFs indicated the deteriorating state of ecological health. However, the forests having proper management had better ecological health i.e., higher species richness, tree density and regeneration. Species richness and contribution of native species was found high in VPFs established before 1980. Analysis across the elevation range reveals higher level of disturbances in VPFs located below 1500 m asl. While higher elevation (above 1500 m asl) performing better both with respect to ecological health and management status. The findings of the study call for urgent attention to bring back the glory of VPFs through policy interventions. Analysis of literature and primary observation suggest that the VPFs in west Himalaya with their existence for over 9 decades are fading the glory due to mismatched policy and practice priorities. The scenario can be changed with appropriate interventions to make these VPFs more relevant for local people as well as the emerging global targets of conservation and sustainable development. Highlights: Assessment was made on ecological condition and management status of VPFs. Out of 1158 documents reviewed on CFs across the globe, 91 are related to VPFs. Results reveals poor management and ecological health of most of the studied VPFs. Ecological health of VPFs situated above 1500 m is comparatively better to < 1500 m. Community rights and financial incentives is essential for better management of CFs.